Analisis Quality Control Buah Naga (Studi Kasus di UD Sabila Farm Kabupaten Sleman): Analysis of Dragon Fruit Quality Control (Case Study at UD Sabila Farm Sleman Regency) - Hasanah, Uswatun; Windani, Isna; Azizah, Wafiq (Jurnal Riset Agribisnis dan Peternakan, 2023)
This study aims to: (1) Know the quality control from the cultivation process to the dragon fruit harvest so that it is ready to be marketed which is applied by UD Sabila Farm. (2) Knowing the criteria and quality standards of dragon fruit cultivated by UD Sabila Farm. (3) Knowing the efforts made by UD Sabila Farm in preventing and correcting the discrepancy in the quality of dragon fruit products. The research design was carried out using a descriptive method. The research location was carried out at UD Sabila Farm which is located in Pakembinangun, Pakem, Sleman, Yogyakarta Special Region. Implementation method using descriptive method. The results showed that the quality control process for dragon fruit was the selection of cultivation sites, climbing poles, intensive care, pest control, harvesting, sorting, packaging, and marketing. The quality criteria and standards applied in the harvesting of Sabila Putih and Red Sabila dragon fruit include the overall level of maturity, meeting the specified grade with a selling price of super grade Rp. 30,000/kg, grade A Rp. 25,000/kd, and grade B Rp. 20,000/kg. Efforts to deal with discrepancies with the processing of dragon fruit in the form of juice, slices and pudding, as well as liquid organic fertilizer.